Accelerating systems thinking in health: Perspectives from the region of the Americas - Rocio, Saenz; María Paulina, Echandi; Karol, Rojas; Luis Fernando, Solís; Ingrid, Gómez (Frontiers in Public Health, 2023)
Introduction: The Systems Thinking Accelerator (SYSTAC) is a community to engage, connect and collaborate to elevate the field of systems thinking with a focus on low- and middle-income countries, highlighting the need to identify existing capacities within research and at the practice level. The study aimed to explore if there is a perceived need for and benefit from the application of Systems Thinking tools for analysis and diagnosis of problem-solving within Healthcare in the Region of the Americas in 2021 and the existing capabilities. Methods: The identification and deconstruction of the needs, demands, and opportunities regarding systems thinking in the Americas were approached by: (i) adapting the tools and Systems Thinking definition to reflect regional nuances, (ii) identifying stakeholder exercise, (iii) needs assessment survey distribution, (iv) stakeholder mapping analysis, (v) workshop. More information on the adaptation and execution of each tool can be found below. Results: 123 stakeholders were identified, of which 40 participated in the needs assessment survey. 72% of respondents indicated little knowledge of the tools and approaches of systems thinking but a high interest in developing them, as stated by 87% of respondents. Qualitative tools were most frequently used, such as brainstorming, problem trees, and stakeholder mapping. Systems thinking is mainly used when conducting research, implementing, and evaluating projects. A clear need and want for training and developing capacities in health systems thinking were identified. However, in practice, systems thinking faces challenges like resistance to change and to the transformation of health processes, barriers at the institutional level, and other administrative disincentives that hinder its application, being institutional transparency, political will, and the articulation of the actors the main challenges. Discussion: Strengthening and building personal and institutional capacities in systems thinking theory and practice requires overcoming challenges such as lack of transparency and inter-institutional cooperation, the low political will to implement it, and difficult stakeholders’ integration. As a first step, it is crucial to understand further the stakeholder network and the capacity needs of the region, gain buy-in from strategic players to establish the use of system thinking as a priority, and develop a roadmap.